Associations between running activities and odds of scoring goals during professional soccer matches - Rampinini, E.; Martin, M.; Riva, N.; Riggio, M.; Donghi, F.; Coutts, A. J. (Research in Sports Medicine, 2025)
We aimed to assess the associations between physical activities of reference teams or the differences with their opponents, and the goals scored in professional soccer. Total distance (TD), distance >20 km/h (VHS) and goals scored during matches of the Serie-A by two Best and two Worst Teams and by their opponents were collected. Odds ratio (OR) of scoring goals when high or low levels of running, as well as higher or lower levels compared to their opponents, were estimated. Performing higher TD than the opponents increased the OR of scoring goals for Best and Worst Teams in 5-min (19.8 ± 5.2, 16.1 ± 7.3) and 15-min (11.5 ± 3.3, 11.5 ± 4.9) intervals. Performing more VHS than the opponents increased the OR of scoring for Best and Worst teams in 5-minute (3.7 ± 0.9, 2.5 ± 0.6) and for Best teams in 15-minute (3.3 ± 1.1) intervals. Odds of scoring were higher when relative differences in running activities between teams, instead of absolute levels, were considered.